Islamic Economic Perspective: Integration of Production, Distribution, and Factor Pricing (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to Determination of factor prices is an essential element in the economic system that includes aspects of production and distribution. In the perspective of Islamic economics, factor pricing not only relies on economic efficiency, but must also pay attention to the principle of distributive justice in line with Islamic values. The research method uses a qualitative approach with a literature review or library reaseach. The data used in this study are sourced from various literature books and scientific articles. The results of the study discuss the concept of factor pricing based on the theory of marginal products, labor markets, time allocation, equilibrium, and return on investment without usury. The analysis focused on the link between economic efficiency and fair distribution in accordance with maqashid sharia. The results show that optimal factor pricing within a sharia framework can support market equilibrium, increase labor productivity, and promote income distribution across different sectors of the economy. In addition, sharia-based policy interventions are needed to overcome market distortions and ensure the realization of holistic economic justice.